Association of Pancreatic Fatty Infiltration With Pancreatic Ductal Adenocarcinoma - Hori, Mika (Nature Publishing Group, 2014)
OBJECTIVES: Fatty infiltration (FI) in the pancreas is positively correlated with high body mass index (BMI) or obesity, and the prevalence of diabetes mellitus (DM), which are well-known risk factors of pancreatic cancer. However, the association of FI in the pancreas with pancreatic cancer is unclear. Recently, we have shown that Syrian golden hamsters feature FI of the pancreas, the severity of which increases along with the progression of carcinogenesis induced by a chemical carcinogen. To translate the results to a clinical setting, we investigated whether FI in the pancreas is associated with pancreatic cancer in a series of patients who had undergone pancreatoduodenectomy. METHODS: In the series, we identified 102 cases with pancreatic ductal adenocarcinoma (PDAC) and 85 controls with cancers except for PDAC. The degree of FI was evaluated histopathologically from the area occupied by adipocytes in pancreas sections, and was compared between the cases and controls. RESULTS: The degree of FI in the pancreas was significantly higher in cases than in controls (median 26 vs. 15%, P<0.001) and positively associated with PDAC, even after adjustment for BMI, prevalence of DM and other confounding factors (odds ratio (OR), 6.1; P<0.001). BMI was identified as the most significantly associated factor with FI in the pancreas. CONCLUSIONS: There is a positive correlation between FI in the pancreas and pancreatic cancer.